IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DI SD NEGERI LANDAH LOMBOK TENGAH - Muhamad Ridwan Habibi; Meri Yuliani; Syaipul Pahru; Muhamad Irzan (LPPM Institut Pendidikan Nusantara Global, 2023)
The focus in this research is; 1) How is the Implementation of Character Education Management at SDN Landah Central Lombok; 2) How is the effort to cultivate character values. This type of deep qualitative research with pedagogical, sociological and psychological approaches. The data collection instrument is the researcher himself as the key instrument. The data collection techniques are observation, interviews and documentation. In analyzing the data carried out in three stages, namely: data reduction, data presentation and drawing conclusions. The research results conclude that; 1) The implementation of character education at SDN Landah Central Lombok is very good. The implementation of character education at SDN Landah Central Lombok can be seen from the aspects of lesson planning, organizing and implementing aspects of character education; 2) Efforts to instill character values at SDN Landah Central Lombok, namely through the teacher's exemplary process which can then be imitated by students.